2023
DOI: 10.3390/cancers15153904
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Patients with Primary and Secondary Myelofibrosis According to the Genomic Classification Using Targeted Next-Generation Sequencing

Abstract: Myelofibrosis (MF) is a heterogeneous disease regarding its mutational landscape, clinical presentation, and outcomes. The aim of our work is to evaluate the genomic classification of MF considering whether it is primary or secondary. One-hundred seventy-five patients, 81 with primary MF (PMF) and 94 with secondary MF (SMF) were hierarchically allocated into eight molecular groups. We found that TP53 disruption/aneuploidy (n = 16, 9%) was more frequent (12% versus 6%) and showed higher allele burden (57% versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…Patients who do not have mutations in any of the three genes mentioned are defined as triple-negative [4]. Finally, further mutations have recently been identified that concern important gene types, including epigenetic modifiers [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who do not have mutations in any of the three genes mentioned are defined as triple-negative [4]. Finally, further mutations have recently been identified that concern important gene types, including epigenetic modifiers [5,6].…”
Section: Introductionmentioning
confidence: 99%